Preparation and Characterisation of a Cyclodextrin-Complexed Mānuka Honey Microemulsion for Eyelid Application - Ilva D. Rupenthal; Priyanka Agarwal; Benedict Uy; Jaeun Kim; Angela A. Cunningham; Ali Seyfoddin; Simon Swift; Jennifer P. Craig (MDPI AG, 2022)
Honey has been widely purported as a natural remedy due to its antimicrobial and anti-inflammatory effects. In recent years, several studies have suggested that the considerably high methylglyoxal (MGO) concentration in Mānuka honey (MH) makes it particularly effective to manage bacterial overload, such as that observed in blepharitis. However, the poor solubility, high viscosity, and osmolarity of aqueous honey solutions, especially at the high MGO concentrations studied in the literature, render the formulation of an acceptable dosage form for topical application to the eyelids challenging. Here, the antibacterial properties of raw MH and alpha-cyclodextrin (α-CD)-complexed MH were evaluated at relatively low MGO concentrations, and a liquid crystalline-forming microemulsion containing α-CD-complexed MH was formulated. After determining pH and osmolarity, ocular tolerability was assessed using human primary corneal epithelial cells and chorioallantoic membranes, while the antibacterial efficacy was further evaluated in vitro. The α-CD-MH complex had significantly greater antibacterial activity against Staphylococcus aureus than either constituent alone, which was evident even when formulated as a microemulsion. Moreover, the final formulation had a physiologically acceptable pH and osmolarity for eyelid application and was well-tolerated when diluted 1:10 with artificial tear fluid, as expected to be the case after accidental exposure to the ocular surface in the clinical setting. Thus, a safe and efficient MH dosage form was developed for topical application to the eyelids, which can potentially be used to support optimal eyelid health in the management of blepharitis.